Probiotic lactic acid bacteria for applications in vegetarian food products - Charernjiratrakul, W.; Kantachote, D.; Vuddhakul, V. (Songklanakarin Journal of Science and Technology (SJST), 2007)
Total of 225 isolates of lactic acid bacteria were isolated from 152 samples of various fermented foods. The strains were investigated for their probiotic properties based on stability in bile salt (0.30%) and high acidity (pH 3), growth under both aerobic and anaerobic conditions, ability to grow without vitamin B12. According to the above criteria, 40 isolates were selected. Using an agar spot method, 16 isolates were able to inhibit Salmonella typhimurium, S. typhi, S. enteritidis, S. paratyphi and 4 strains of E. coli O157 : H7 as clear zone greater than 10 mm. Moreover, utilization of protein or fat or starch was also considered. Only 5 isolates were able to utilize protein and further selected for antibiotics sensitivity test. The selected isolates were susceptible to following antibiotics: ampicillin, chloramphenicol, erythromycin , kanamycin, tetracycline and vancomycin; however they were resistant to ceptazidime and norfloxacin. They all showed better growth in vegetarian medium (coconut juice medium) than MRS medium both under static and shaking conditions. Five active isolates were identified as Lactobacillus plantarum LL13, LN18, LP11, LS35 and Pediococcus pentosaceus LT02 by API 50 CH system. All cultures grew well in carrot juice by reducing pH from 6.4 to below 4.0 after 24 h of fermentation at 35oC. The lactic cultures in fermented carrot juice lost their viability about 2 log cycles after 15 days of cold storage at 4oC.